A Compact Dual-Band Quasi-Elliptic Filter Based on Hybrid SIW and Microstrip Technologies - Zhu, Yilong; Dong, Yuandan (IEEE transactions on circuits and systems. II, Express briefs, 2022)
In this brief, by combining substrate integrated waveguide (SIW) and microstrip technologies, a novel dual-band filter is proposed to achieve a quasi-elliptic response for both passbands. The dual-mode characteristics of the SIW cavities, namely TE 101 and TE 201 modes, are used to create two passbands. Different with the conventional inductive windows, two pairs of uniform impedance resonators (UIRs) with electric mutual coupling, which are etched between the two rectangular SIW cavities, are used to couple the TE 101 and TE 201 modes, respectively. Good merits are achieved in this way, including: 1) Independent coupling paths are created for TE 101 and TE 201 modes, which would reduce the complexity of numerical optimization; 2) Since the electric couplings are generated between each pair of the UIRs, it would be easy to realize a cross coupling by only constructing inductive windows between the SIW cavities. A filter prototype with central frequencies operated at 8 GHz and 10 GHz is then designed and fabricated for validation, which shows a compact size and high selectivity with controllable transmission zeros.